2016
DOI: 10.1016/j.paid.2016.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism explains variance in self-defeating behaviors beyond self-criticism: Evidence from a cross-national sample

Abstract: (2016) Perfectionism explains variance in self-defeating behaviors beyond self-criticism: Evidence from a cross-national sample.Personality and Individual Differences, 295 British), this study examined whether evaluative concerns perfectionism (socially prescribed perfectionism, concern over mistakes, doubts about actions) explained variance in self-defeating behaviors (binge eating, procrastination, interpersonal conflict) after controlling for selfcriticism. Results showed that-after controlling for self-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
2
23
0
3
Order By: Relevance
“…The correlations with PS, however, are considerably smaller than those with PC (e.g., Dunkley, Zuroff, & Blankstein, 2006). This pattern PARTIALLING PERFECTIONISTIC STRIVINGS AND CONCERNS 6 of relations suggests that self-criticism is closely related to PC, but not to PS (Dunkley et al, 2006;Sherry, Stoeber, & Ramasubbu, 2016). Consequently, evidence is lacking to suggest that either conditional self-acceptance or self-criticism should be considered defining characteristics of PS.…”
Section: Is Partialling Perilous or A Theoretically Informative Appromentioning
confidence: 83%
“…The correlations with PS, however, are considerably smaller than those with PC (e.g., Dunkley, Zuroff, & Blankstein, 2006). This pattern PARTIALLING PERFECTIONISTIC STRIVINGS AND CONCERNS 6 of relations suggests that self-criticism is closely related to PC, but not to PS (Dunkley et al, 2006;Sherry, Stoeber, & Ramasubbu, 2016). Consequently, evidence is lacking to suggest that either conditional self-acceptance or self-criticism should be considered defining characteristics of PS.…”
Section: Is Partialling Perilous or A Theoretically Informative Appromentioning
confidence: 83%
“…También se ha asociado a una alta capacidad intelectual, buenas calificaciones, creatividad, a un alto estándar de rendimiento y planificación profesional (Chan, 2009;Sastre-Riba, 2012, Stoeber, Mutinelli y Corr, 2016Stoeber y Otto, 2006). En contraparte, el perfeccionismo insano implica una actitud autocrítica desmedida, tendencia a la preocupación excesiva por los errores, pensamiento dicotómico (todo o nada), intolerancia al fracaso, inseguridad en relación a los logros personales y autodepreciación cuando éstos no son alcanzados (Castro-Fornieleset al, 2007;Frost, Marlen, Lahart y Rosenblate, 1990;Sherry, Stoeber y Ramasubbu, 2016). De acuerdo a Slaney, Rice, Mobley, Trippi y Ashby (2001), el elemento que distingue al perfeccionismo sano del desadaptativo es la discrepancia entre los altos estándares autoimpuestos y el desempeño percibido.…”
Section: Introductionunclassified
“…Los individuos con perfeccionismo desadaptativo tienen una mayor prevalencia a experimentar síntomas del desorden afectivo, como depresión y ansiedad (Abdi, Gholamreza Chalabianloo, Joorbonyan, 2015;Egan, Wade y Shafran, 2011), y a presentar actitudes y conductas alimentarias de riesgo (Boone, Soenens, Braet, y Goossens, 2010;Dour y Theran, 2011;Sherry, Stoeber y Ramasubbu, 2016), estrategias disfuncionales para enfrentar el estrés (Sirois y Molnar, 2014), adicción al trabajo (Stoeber, Davis y Townley, 2013) e inclinación suicida (Kiamanesh, Dyregrov, Haavind y Dieserud, 2014;Rasmussen, Slish, Wingate, Davidson y Grant, 2012), entre otras características perjudiciales.…”
Section: Introductionunclassified
“…Perfectionism is a personality trait associated with a preoccupation with accuracy (e.g., Sherry, Stoeber, & Ramasubbu, 2016;Stoeber, 2011;Stoeber & Eysenck, 2008;see Flett, Nepon, & Hewitt, 2016, for a review). The present study, therefore, investigated the involvement of perfectionism in false memories processes.…”
Section: Introductionmentioning
confidence: 99%
“…Perfectionistic strivings is described as the tendency to set extremely high personal standards, whereas perfectionistic concerns refers to the tendency to be worried and over-preoccupied with making mistakes and with feelings of discrepancy between one's standards and performance (e.g., Lo & Abbott, 2013;Sherry et al, 2016;Stoeber, 2011). Studies have revealed numerous characteristics associated with perfectionistic strivings and perfectionistic concerns.…”
Section: Introductionmentioning
confidence: 99%